Intermediate state of hexagonal close-packed structure to face-centered cubic structure transformation: Direct evidence for basal-type face-centered cubic phase via partial dislocation in zirconium. (30th January 2022) - Yuan, Fusen; Han, Fuzhou; Zhang, Yingdong; Muhammad, Ali; Guo, Wenbin; Ren, Jie; Liu, Chengze; Gu, Hengfei; Li, Geping; Yuan, Gaihuan
Highlights: Intermediate state of B-type FCC zirconium phase was firstly reported. B-type FCC phase obey the path of HCP→Intermediate state→FCC. Intermediate state is direct evidence of FCC phase via partial dislocation. Abstract: An intermediate state of basal-type (B-type) face-centered cubic (FCC) zirconium phase is firstly reported in as-solidified pure zirconium by means of transmission electron microscopy (TEM) technique. The B-type hexagonal close-packed (HCP) to FCC phase transformation can be realized by following path: HCP→Intermediate state→FCC and each stage contained Shockley partial dislocations with Burgers vector of 1 / 6 [ 0 1 ¯ 10 ] . The observed intermediate state is direct evidence of the B-type FCC zirconium phase via partial dislocation.